2019
DOI: 10.1002/mgg3.548
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR‐200a and miR‐204 in MPP+‐treated differentiated PC12 cells as a model of Parkinson’s disease

Abstract: Background Parkinson's disease (PD) is ranked as the second most common neurodegenerative disorder caused by loss of dopaminergic neurons in the substantia nigra. Micro(mi)RNAs are a class of small noncoding RNAs that regulate gene expression and aberrant expression of them is closely correlated with many neurodegenerative conditions including PD. Silent information regulator 1 ( SIRT1 ) as a known deacetylase and B‐cell lymphoma‐2 ( BCL2 ) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…MPP+ is a common dopaminergic neurotoxin that is widely used in in vitro PD models. According to previous report [ 16 ], differentiated PC12 cells were treated with 800 μ M MPP+ for 24 hours. The MTT assay had been preciously used to examine the cell viability of MPP+-treated PC12 cells [ 16 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MPP+ is a common dopaminergic neurotoxin that is widely used in in vitro PD models. According to previous report [ 16 ], differentiated PC12 cells were treated with 800 μ M MPP+ for 24 hours. The MTT assay had been preciously used to examine the cell viability of MPP+-treated PC12 cells [ 16 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to previous report [ 16 ], differentiated PC12 cells were treated with 800 μ M MPP+ for 24 hours. The MTT assay had been preciously used to examine the cell viability of MPP+-treated PC12 cells [ 16 18 ]. The MTT assay showed that cell viability was decreased after MPP+ treatment ( Figure 2(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of miR-200a was significantly up-regulated in the pheochromocytoma cell line PC12 cells and SH-SY5Y cells following exposure to MPP + that leads to the induction of oxidative stress and cell apoptosis (Salimian et al, 2018;Talepoor Ardakani et al, 2019). Additionally, the transcript level of SIRT1 (a miR-200a target) showed significant down-regulation in the MPP + -treated cells, confirming that SIRT1 may induce DA neuronal apoptosis via P53 and FOXO signaling pathways (Salimian et al, 2018).…”
Section: Mir-200amentioning
confidence: 82%
“…Also a study on brain tissue of EAE mice displayed miR-141 overexpression suggesting the potential role of this microRNA in MS [36]. In 2018, two separate studies by our colleagues showed upregulation of miR-141 and miR-200a in MPP+-treated differentiated PC12 cells as a model of Parkinson's disease [37,38]. In our previous study it has been also revealed that both microRNAs expression level and frequency of Th17 cells were higher in MS patients compared to healthy groups [27].…”
Section: Discussionmentioning
confidence: 99%